RANCANG BANGUN ALAT PEMINDAH GALON - Pratama, Dandy; Tri Wardhana, Ganang; Subkhan; Idiar (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
The Bangka Belitung region is a province in Indonesia with abundant water resources. However, the water quality in this area often does not meet health standards, prompting residents to seek alternative sources of clean and hygienic drinking water. One chosen solution is refillable drinking water depots. One such depot is Alam Water, located in Air Ruai, Pemali District, Bangka Regency, Bangka Belitung Islands. However, the process of transferring gallons from the filling station to the distribution truck is still done manually by workers, leading to suboptimal productivity. This study aims to design and create a gallon transfer tool capable of transporting two 18.92-liter gallons. The research method follows the VDI 2222 methodology, which includes planning, concept, design, and completion stages. The result of this method is the development of a gallon transfer tool capable of transporting two 18.92-liter gallons, tested by transferring gallons from the filling station to the distribution truck 25 times, with a total time of 365.02 seconds or approximately 6.083 minutes.